Pengaruh Perencanaan Pajak, Beban Pajak Tangguhan, dan Financial Distress Terhadap Manajemen Laba - Shafira Nurulita; Tri Utami (AKUA: Jurnal Akuntansi dan Keuangan, 2024)
The study aims to determine the effect of tax planning and deferred tax expanse on earnings management in consumer non-cyclicals companies listed on the Indonesia Stock Exchange in 2018-2022. The population in this study were 113 companies and the research sample was 30 companies within a period of 5 years. The sampling technique used in this study is using sampling techniques. The data used is quantitative data sourced from secondary data, then the data collected is analyzed using descriptive analysis methods, classical assumption testing and hypothesis testing. Hypothesis testing in this study using panel data regression with t test and F test. Based on the results of the study shows that simultaneously tax planning, deferred tax burden, and financial distress have a significant effect on profit management. And the test results partially show that tax planning does not have a significant negative effect on profit management, tax burden has a significant negative effect on profit management, and financial distress does not have a significant negative effect on profit management.